2021
DOI: 10.1080/23802359.2021.1970638
|View full text |Cite
|
Sign up to set email alerts
|

First report of the complete mitogenome of Microchironomus tabarui Sasa, 1987 (Diptera, Chironomidae) from Hebei Province, China

Abstract: Microchironomus tabarui Sasa, 1987 is an important bioindicator for freshwater ecosystem monitoring. Although COI barcode analyes have been performed on M . tabarui , the mitogenome of this taxon has not been assembled and analyzed. Here the complete mitogenome of M . tabarui was sequenced and analyzed to confirm the systematic and phylogenetic history of this species. The mitogenome is 15,667 bp long with hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…3CZ (Supplementary Table S3). The highest and lowest frequent codon families are Phe and Cys, respectively (Supplementary Figure S1), which is congruent with those of previously published chironomid species [32][33][34][35]. The Ka/Ks value (ω) is used to test for signatures of natural selection.…”
Section: General Features Of Stenochironomus Mitogenomessupporting
confidence: 83%
See 1 more Smart Citation
“…3CZ (Supplementary Table S3). The highest and lowest frequent codon families are Phe and Cys, respectively (Supplementary Figure S1), which is congruent with those of previously published chironomid species [32][33][34][35]. The Ka/Ks value (ω) is used to test for signatures of natural selection.…”
Section: General Features Of Stenochironomus Mitogenomessupporting
confidence: 83%
“…Published mitogenome data of Chironomid are relatively rare compared with other insects of Diptera. Previous studies have focused on the genome organization and the application of nucleotide sequence information in phylogenetic analysis [30][31][32][33][34][35][36][37]. However, mitochondrial gene rearrangement has never been reported in the Dipteran family Chironomidae.…”
Section: Introductionmentioning
confidence: 99%
“… 2022 ), MZ261913 (Kong et al. 2021 ), MZ981735 (this study), MW677959 (Lei et al. 2021 ), MZ043575 (Lin, Liu, et al.…”
Section: Resultsmentioning
confidence: 54%
“…However, a recent study has reported the mitochondrial gene rearrangement in Chironomidae for the first time (Zheng et al, 2022). There is still a lack of further research on the mitogenomes of Chironomidae (Beckenbach, 2012; Deviatiiarov et al, 2017; Fang et al, 2022; Kim et al, 2016; Kong et al, 2021; Lei et al, 2021; Zheng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%